Modified Isoinertial-Based Ruffier Test in Healthy Individuals: A Feasibility Study - Bruno Trovato; Federico Roggio; Luca Petrigna; Giuseppe Musumeci (Journal of Functional Morphology and Kinesiology, 2023)
Cardiorespiratory fitness is an essential indicator in sports science and sports medicine that can be assessed with several tests. The Ruffier test is a submaximal test valid to estimate maximum oxygen uptake; it consists of 30 squats in 45 s, which may be challenging for inexperienced individuals. This study aims to verify the feasibility of a modified inertial-based version of the Ruffier test to assess cardiorespiratory fitness with 10 squats in 15 s. Both classic and isoinertial Ruffier tests were administered to thirty-five healthy young adults (20 men and 15 women), age 22.06 ± 2.13 years, BMI 23.87 ± 2.74. The two one-sided test confirmed the comparability of the isoinertial Ruffier test with its classic version within equivalence bounds of ±3.726. Furthermore, gender, age, body weight, the difference between peak heart rate after isoinertial squatting and resting heart rate, and the isoinertial Ruffier index are the coefficients of our best VO2max prediction model with an adjusted R2 of 0.937, sensitivity of 0.89, and specificity of 0.81. The study evidenced the feasibility of the isoinertial Ruffier test to measure cardiorespiratory fitness through a quick, safe, and short squat test easy to perform in fitness centers and primary care clinics.